Penerapan SDGs-Based Entrepreneurship dan Aksi Hijau Kampus Berdampak melalui Penanaman Pohon dan Edukasi Lingkungan di Deli Serdang dan Kota Medan - Juli Meliza; Zuhri Zuhri; Kartika Kartika (Jaanur Elbarik Indonesia, 2026)
This community service activity aimed to restore critical urban and coastal ecosystems while instilling a Sustainable Development Goals (SDGs)-based entrepreneurship mindset among academic community members. The program was conducted at the Canal Urban Forest in Medan on June 22, 2026, and the Coastal Area of Deli Serdang Regency on June 23, 2026. The method integrated Community-Based Development (Comdev) and Asset-Based Community Development (ABCD) approaches through three stages: preparation, action-oriented planting with educational briefings, and sustainability evaluation. Target participants comprised the STIM Sukma Medan team (lecturers and students), coastal residents, urban forest visitors, and officers from the Ministry of Public Works. Results demonstrated the successful planting of 600 trees (100 shade trees and 500 mangrove seedlings) with an initial survival rate exceeding 85%, transformed mindsets toward impact-oriented entrepreneurship, and strengthened cross-sectoral collaboration.